Factors associated with adolescent malnutrition among Nigerian students - Abdulkarim, Aishatu Ahmed; Otuneye, Adekunle T; Ahmed, Patience; Shattima, Dennis R (Bangladesh Journal of Medical Science, 2016)
Objectives: The objective of this study was to determine the factors associated with malnutrition among adolescents. Design: This was a cross-sectional study conducted among adolescents (10-19 years) in secondary schools. A multistage sampling technique was employed. Setting: Senior secondary schools in The Abuja Municipal area council, Federal Capital Territory, Nigeria. Participants: A total of 1700 students from 8 selected schools. All schools in the Abuja Municipal Area council (AMAC) were stratified into urban and rural schools. Eight schools were selected by balloting from a list of schools obtained from the Education centre. A school was selected from each of the four major districts of AMAC and four schools were selected from the rural making a total of 8 schools. Although the consent of the school authorities was obtained, individual subject also consented to the study before being enrolled. Study: The study excluded those adolescents who were physically challenged thus limiting physical activity. Sociodemographic information was obtained using an interviewer administered questionnaire. Subjects height and weight was taken using the floor-type height (H) and weight (W) measuring scale model ZT-120 using Massachusetts Department of Public Health Protocol. Main outcome measure: The nutritional status was determined using the formula: BMI= W/H2, where W=weight (in kilograms) and H=height (in meters). The age and sex specific height and BMI percentile for each subject was determined using the 2007 WHO Height and BMI growth charts for age 5-19 years. The students were then classified into one of the following categories using previously used standards: normal, stunted, wasted, overweight or obese. Data was analyzed using SPSS version 17 statistical package. A regression analysis of all investigated factors was done to determine those with significant association to malnutrition. Results: The mean age was 14.43±1.94 years; male 688, female 862, M:F ratio 1.1.3. Mean BMI, weight and height were 20.31±3.07kg/m2, 51.07±10.80 kg, and 157.88±9.33 cm. The prevalence of overweight, stunting, obesity and wasting was documented as 13.2% (205/1550), 11.3% (175/1550), 2.6% (41/1550) and 1.7% (27/1550) respectively. Low social class, male gender, hawking after school and rural setting were associated with stunting (p<0.05) and female gender and watching Television for more than 3 hours daily were associated with overweight (p<0.05). Obesity occurred more in urban areas. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.243-248